Goods Inventory Information Systems Based on the Fast Concept at SDN 07 Sidang Danau - Effendy, Irman; Sarwanto (Journal of Computer Networks, Architecture and High Performance Computing, 2023)
Inventory data collection activities in schools are still manual and the data tracking system is not yet available because the inventory data collection system in schools is not well managed so that it often makes it difficult to search for data on existing items. The inventory data collection system running at SDN 07 Sindang Danau still uses a simple computerized system utilizing standard office (Microsoft Office Excel and Word). This allows for many errors in processing inventory data, and causes inventory data collection managed by SDN 07 Sindang Danau to be less efficient. , As well as resulting in difficulties in searching for data and taking up a relatively long time in preparing reports. To help solve this problem, it is necessary to have a web-based inventory data system using the FAST concept (framework for the application of system thinking) which has 6 stages of scope definition, problem analysis, requirements analysis, logical design, decision analysis and physical design.